(untitled) - Ostrikov, Kostya (Ken) (Weinheim, 2007)
This monograph covers most essential things an advanced researcher needs to know attempting to fabricate exotic nanostructures and intricate nano-arrays in low-temperature plasma environments. In an easy-to-follow and systematic way, the book reveals the state-of-the art "know-hows" gained from authors work in this area: how to generate and control the plasma, how to develop suitable plasma nanofabrication facilities, how to tailor the plasma-based process to synthesize specific nanostructures and several others. Various examples of successful applications of plasma-aided nanofabrication include synthesis and post-processing of carbon nanotubes and other high-aspect-ratio nanostructures, microporous films, low-dimensional quantum confinement structures, bioceramic coatings, and other nanocrystalline and nanostructured materials with a broad range of applications ranging from protective and functional coatings to biogenetic and nanoelectronic devices. The level of complexity in this book varies from the common knowledge to the expert level to make it suitable not only to researchers, engineers, and graduate students specializing in relevant areas but also to high school teachers, students and general public interested in nanotechnology.
Keywords: Nanostructured materials,Plasma engineering,Low temperature plasmas,Manufacturing processes